HUBUNGAN KONSENTRASI SUSPENDED PARTICULATE MATTER (SPM) UDARA AMBIEN DAN KONDISI CUACA DENGAN ANGKA KEJADIAN ASMA DI KECAMATAN SEMARANG BARAT TAHUN 2015-2017 - Esti Nurmala; Budiyono Budiyono; Suhartono Suhartono (Jurnal Kesehatan Masyarakat (Undip), 2018)
West Semarang district is one areas that has quite high asthma incidences aged 45-65 years old in 2017 with prevalence of 10,9 per thousand population. The weather changes have an effect on asthma and spread of pollutants in the air. Suspended Particulate Matter (SPM) is one of air pollutions can cause asthma attack by increasing airway reactivity. The study aimed to analyze the relationship between consentration of SPM and weather conditions with the asthma incidences aged 45-65 years old in West Semarang district during 2015-2017. This research was an observational analytic approach with time-based ecological design. Data of SPM and weather conditions were obtained from the Agency for Meteorology, Climatology and Geophysics (BMKG) Semarang, at the station of taking in Klimatologi Kelas I Semarang. Data of asthma incidences were obtained from all primary health care in administrative area of West Semarang district. The results showed that the average SPM during 2015-2017 was 152,76 µg/Nm3; temperature was 28,230C; humidity was 77%; rainfall was 194,72mm/month; wind speed was 5,44 km/hour. The correlation test results between SPM with asthma incidences (p=0,558, r=0,101); temperature with asthma incidences (p=0,323, r=-0,196); humidity with asthma incidences (p=0,540, r=0,106); and rainfall with asthma incidences (p=0,596, r=0,091). The research concluded that there was no significant correlation between SPM and weather conditions with asthma incidences aged 45-65 years old.